2014
DOI: 10.1302/0301-620x.96b1.31905
|View full text |Cite
|
Sign up to set email alerts
|

A novel osseointegrated percutaneous prosthetic system for the treatment of patients with transfemoral amputation

Abstract: Patients with transfemoral amputation (TFA) often experience problems related to the use of socket-suspended prostheses. The clinical development of osseointegrated percutaneous prostheses for patients with a TFA started in 1990, based on the long-term successful results of osseointegrated dental implants. Between 1999 and 2007, 51 patients with 55 TFAs were consecutively enrolled in a prospective, single-centre non-randomised study and followed for two years. The indication for amputation was trauma in 33 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
274
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(285 citation statements)
references
References 30 publications
7
274
1
3
Order By: Relevance
“…A superficial infection was treated with a single 7-day course of oral antibiotics (cephalexin 500 mg). The few authors who have reported on the safety of osseointegrated implants have described an acceptable rate of superficial infection and rare occurrence of other adverse events, including deep infection (Brånemark et al 2014). Altogether, one could hypothesize that the absence of stoma revision and explantation surgeries might be due to techniques adopted to close pathways from the external environment, such as press-fit implantation and soft tissue handling, consequently sealing the knee to ascending infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A superficial infection was treated with a single 7-day course of oral antibiotics (cephalexin 500 mg). The few authors who have reported on the safety of osseointegrated implants have described an acceptable rate of superficial infection and rare occurrence of other adverse events, including deep infection (Brånemark et al 2014). Altogether, one could hypothesize that the absence of stoma revision and explantation surgeries might be due to techniques adopted to close pathways from the external environment, such as press-fit implantation and soft tissue handling, consequently sealing the knee to ascending infections.…”
Section: Discussionmentioning
confidence: 99%
“…Few authors have reported on the safety of this procedure (Brånemark et al 2014, Tsikandylakis et al 2014). One of the largest studies included 51 patients and reported superficial infections in approximately half of these patients at 2-year follow-up.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rickard developed a textured long-bone fixture modified from his father's dental screw design and began an osseointegration program for those with limb loss in Sweden in the 1990s [3]. Subsequently, Horst Aschoff in Germany developed a press-fit implant for transcutaneous osseointegration [2].…”
mentioning
confidence: 99%
“…Most importantly, patient comfort can be dramatically improved by obviating socket related problems and residual limb pain. Aseptic loosening (2%-6%) and periprosthetic fracture (0%-4%) have occurred at relatively low and ostensibly acceptable rates [2,3,6,9]. However, concerns regarding infection by way of the skin-implant interface persist.…”
mentioning
confidence: 99%